1992
DOI: 10.1677/joe.0.1340073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of steroid hormones on cyclic adenosine 3′,5′-monophosphate levels in the rat lung

Abstract: The possible role of cyclic adenosine 3',5'-monophosphate (cAMP) in mediating the action of steroid hormones was investigated using the rat lung. Male rats were adrenalectomized and treated with olive oil, dexamethasone, corticosterone, deoxycorticosterone (DOC) or progesterone. At the end of 10 days, 100 micrograms isoprenaline/kg was injected intraperitoneally 5 min before the animals were killed to stimulate cAMP production. Adrenalectomy significantly decreased cAMP levels in the rat lung. Dexamethasone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Though clinical technology develops fast, the high morbidity and mortality of sepsis is still a major problem [6,7]. Previous studies have shown that septic lung injury can lead to the interaction of cAMP and various hormone levels, resulting in changes in lung tissue structure [8][9][10][11][12]. In this study, the survival rate of 40 SD rats was studied through the CLP sepsis model.…”
Section: Discussionmentioning
confidence: 99%
“…Though clinical technology develops fast, the high morbidity and mortality of sepsis is still a major problem [6,7]. Previous studies have shown that septic lung injury can lead to the interaction of cAMP and various hormone levels, resulting in changes in lung tissue structure [8][9][10][11][12]. In this study, the survival rate of 40 SD rats was studied through the CLP sepsis model.…”
Section: Discussionmentioning
confidence: 99%